Hand Eczema in High School Students in Poland: A Cross-sectional Study - Marta Szepietowska; Alicja Dabrowska; Szymon Dziasek; Bartosz Lisicki; Katarzyna Skinderowicz; Bartosz Wilczyński; Piotr K. Krajewski; Jacek C. Szepietowski (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)